Introductory aspects of the Self through a fractal model: configuration and intersection between stability and change in time, from a personality´ perspective (Revista de Psicología, 2019)
The fractal conception of psychic time posed by Susie Vrobel is inspired by the phenomenology of Husserl’s time, and pre-sents certain characteristics that can be analyzed to the thought of Xavier Zubirí on this question. This fractal con-ception occurs in the complexity and differentiation of the details of temporal events. The vision of the Self from the perspective of the Personality, through the theory of non-linear dynamic systems (NDS), addresses a wealth of con-structs that re-describe the notions of stability and linear change over time, through self-organization, complexity, emerging phenomena, among others. The experience of time is postulated as an experience of affective intellection for the prospective psychic liberation.
Keywords: Self; fractal; complexity; emergent phenomena; psyche’s time.